The complexity and dynamics of enhancing endurance performance - Chappell, Sarwat K., author; Shahroudi, Kamran Eftekhari, advisor; Troxell, Wade, committee member; Conrad, Steve, committee member; Vijayasarathy, Leo, committee member (Colorado State University. Libraries, 2026)
Enhancement of endurance performance has been a longstanding goal for professional athletes, military personnel, as well as health-conscious individuals. Traditional methods to improve endurance primarily focus on individual changes in physiology with training. Recent trends generally recognize that mental stress affects endurance and that psychological interventions can affect behaviors that sustain activity. Current methods treat physiological and psychological factors separately in different disciplines as linear processes with one-size fits all solutions. This representation fails to capture the evolving dynamic interactions and feedback loops between physical and mental endurance attributes over long duration sustained activity which vary with individuals. This mental model could be why the United States civilian and military population suffer from higher rates of obesity and mental health diagnoses than many global peers, despite spending the most on fitness and wellness. The gap in research is that there are no combined behavioral, mental, and physical system dynamical models for endurance. This dissertation develops new Systems Dynamical models that combine behavioral, mental, and physical aspects of endurance. These models account for individual variability in physical, mental and behavioral factors that affect endurance and capture the dynamic feedback loops between them that result in the evolution of physical and mental endurance over time. To accomplish this, the research applied a Model Based Systems Thinking (MBST) approach that utilizes a suite of tools including causal loop diagrams, agent-based modeling, system dynamical causal modelling as well as rigorous analyses to simulate the complex, evolving interactions between physical, mental and behavioral factors that affect endurance. The primary contribution of this research is a set of Endurance models that enable understanding and predicting how changes to activity affect physical and mental endurance over time. This enables tailoring training methodologies to individual physical and mental factors allowing for a balance between physical and mental endurance enabling sustained activity. This research provides an Endurance Power(EP) metric that captures the effect of perception of effort on ability to perform an activity. This can prevent overtraining and stopping an activity due to mental stress. The dissertation provides strategies based on model insights that enable tailoring training for civilian and warfighter groups and individuals to optimize endurance enhancement over time.
Keywords: systems thinking; physiology; agent modelling; systems dynamics